THIS UZBEKISTANAD CORPORATION CAN BE AN INDEPENDENT JOINT-STOCK COMPANY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
About the general meeting of shareholders, about the supervisory board of the company, about the executive body (respective director, board, trustee) within three months from the date of state registration on) and the audit commission (inspector) must prepare the regulations defining their activity procedure, rights and obligations, as well as the decision-making procedure by these bodies of the company, and approve them at the general meeting of shareholders.